Expression of nuclear transcription factor interferon consensus sequence binding protein in chronic myeloid leukemia correlates with pretreatment risk features and cytogenetic response to interferon-α - Schmidt, Manuel; Hochhaus, Andreas; Nitsche, Andreas; Hehlmann, Rüdiger; Neubauer, Andreas (Blood, 2001)
Recently, it was shown that interferon consensus sequence binding protein (ICSBP), a member of the interferon regulatory factor (IRF) family, has a potential role in chronic myeloid leukemia (CML). Deletion of ICSBP gene in mice leads to a CML-like syndrome and samples from CML patients exhibited impaired ICSBP expression. The present study found that ICSBP expression correlated with risk features determined by Sokal score in untreated CML (P = .007 for high versus low risk). In addition, analyzing ICSBP expression during interferon-α (IFN-α) therapy in “good” (n = 27) versus “poor” (n = 15) cytogenetic responders, high ICSBP levels were only observed in “good” responders (P = .0002). Together, these data suggest that ICSBP levels are related to initial presentation of CML and the therapeutic response of CML to IFN-α, indicating an important role of ICSBP in CML.
Gesehen am 18.05.2022